PERUBAHAN PENCAK SILAT PANGEAN DI KENEGERIAN TELUK BERINGIN KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Rijal, Khairul; Tantoro, Swis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted at Kenegerian Teluk Beringin,, Gunung Toar Subdistrict Kuantan Singingi Regency. The purpose of this research is to find out how the profile of the Pangean Pencak Silat, as well as find out what efforts are being made to keep the Pencak Silat Pangean. Determination of the sample are purposive sampling because the author has set some criteria that will be used as a source of information in the research that will be conducted as many as seven people. The author uses descriptive qualitative methods and instruments of data is the observation and interview. Research results find Pencak Silat Pangean Profile that is the beginning of an influx of Pencak Silat Pangean to Kenegerian Teluk Beringin, figures of the Pencak Silat Pangean, the meanings contained in the Pencak Silat Pangean, and how implementation of Pencak Silat Pangean. Pencak Silat Pangean Swordsman was brought by Sope from Kolang Malaysia, every movement or the existing instruments on the implementation of Pencak Silat Pangean contain meanings that are concerned with the religion of Islam. One of its meaning as a four step symbolizing companions of the Prophet Muhammad SAW. Implementation of Pencak Silat Pangean during Ramadhan, but this time on a typical day there also. With the peak events remain after feast Eid al-Fitr or Eid al-Adha. Efforts are being made to keep the Pencak Silat Pangean is with the way foster a sense of high enthusiasm to members of Pencak Silat Pangean, as well as to people who want to participate. The second is not to restrict the membership of Pencak Silat Pangean. So that anyone can participate in the Pencak Silat Pangean.Keywords: Pencak Silat Pangean, Teluk Beringin.